2013
DOI: 10.1007/s10535-013-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and gene mapping of a chlorophyll-deficient mutant clm1 of Triticum monococcum L.

Abstract: Diploid wheat Triticum monococcum L. is a model plant for wheat functional genomics. Chlorophyll-deficient mutant (clm1) was identified during manual screening of the ethylmethane sulphonate (EMS)-treated M 2 progenies of T. monococcum accession pau14087 in the field. The clm1 mutant, due to significantly decreased chlorophyll content compared with the wild-type (WT), exhibited pale yellow leaves which slowly recovered to green before flowering. The clm1 mutant showed early flowering, reduced number of tillers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…EMS can form adducts with nucleotides, causing them to mispair with their complementary bases and introducing base changes after replication [15]. EMS-induced mutants have been created in rice [16], maize [17], barley [18], diploid wheat [19,20], and hexaploid wheat [21,22]. Some genes, such as klu, regulating seed size [23], and als3-1, required by seedlings for growth in aluminum-toxic environments [24], have been isolated using EMS-induced mutations in Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…EMS can form adducts with nucleotides, causing them to mispair with their complementary bases and introducing base changes after replication [15]. EMS-induced mutants have been created in rice [16], maize [17], barley [18], diploid wheat [19,20], and hexaploid wheat [21,22]. Some genes, such as klu, regulating seed size [23], and als3-1, required by seedlings for growth in aluminum-toxic environments [24], have been isolated using EMS-induced mutations in Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…Artificially induced mutations are produced by various approaches. Many of them are induced with chemicals (Ansari et al, ), radiation (Chen et al, ) and biological agents (Bang et al, ). The frequency of artificially induced mutations is ≤ 3% higher than that of spontaneous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified that most of the leaf color mutants are controlled by a single recessive nuclear gene. For example, many leaf mutants of soybean[33], wheat [36], and rice [37] were all controlled by a single recessive nuclear gene. In addition, there are a few leaf color mutants, in which the traits are controlled by the cytoplasmic gene.…”
Section: Discussionmentioning
confidence: 99%